Perancangan Aplikasi Transaksi Jual Beli Perhiasan Emas berbasis Android - Candra Agustina (Jurnal Teknologi Informasi dan Terapan, 2019)
Gold Shop is a business of buying and selling gold, both in the form of jewelry and in the form of bars. Transactions carried outsell and buy gold jewelry, with different buying and selling prices. In a gold shop, to sell jewelry a clerk needs to write down the weight, and draw the model in a sales letter or memorandum. The problem that occurs is the ability to draw from employees who are not the same, some can draw jewelry similar to the original, some are unclear. Jewelry letters are also sometimes lost in the hands of customers so when selling must first ascertain whether the jewelry originates from this store. Therefore, it is necessary to make an information system to facilitate the process of buying and selling gold jewelry. The system is made based on Android because it can utilize the mobile phones of each employee. The system is made using the Rapid Application Development method, to get the final result of an android-based application. This method consists of 3 stages, namely the needs plan, the system design process, and implementation. This gold jewelry sale and purchase application consists of 2 users namely shop owners and employees. The function of the owner application is to see the number of items sold jewelry purchased, daily, weekly and monthly financial statements. The application has the advantage of updating the price of gold, both selling and buying in realtime. Using this application can speed up transactions, create reports, and reduce errors in recording transactions.